ANDROID-BASED EMPLOYEE DATA INFORMATION AND SALARY VERIFICATION SYSTEM - Nurdhini, Gina; Sukma Indrayana, Andri; Wirasto, Anggit (LKP Tematik Aperta Nusantara, 2025)
Piranti Teknik Indonesia is engaged in manufacturing which produces wiring harnesses for motorcycles and others. This company is one of the companies that joined the Banshu Group or known as Banshu Electric Indonesia. PT. Piranti Teknik Indonesia is one that uses a computerized but simple payroll system, but in the salary complaint system it is still done manually, so the data processing is experiencing obstacles. If this problem is allowed to continue it will result in the work system being less effective. So we need a system that is able to provide convenience in managing salary data efficiently. For this reason, the author will design an android-based information system that will facilitate the process of complaining about salary data by using a computerized system and data base as storage media, so that data will not be lost or damaged. With the construction of an Information System, the payroll process will no longer be hampered, because this system is designed to build a work system that is more effective, fast and accurate. If this research is successful, it will produce a system that is able to help provide convenience for both parties, so that it can be expected that later it will simplify and speed up the service process, data storage and, as well as the restatement of the data.